100 years – life goes on (a clinical case) - V. I. Kryvenko; S. P. Pakhomova; O. P. Fedorova; I. S. Kachan; O. A. Svitlytska; L. V. Herasymenko (Zaporožskij Medicinskij Žurnal)
The aim of this work is to draw attention to the peculiarities of long-lived patient functioning and to assess the state of health in a 100-year-old patient, her cognitive functions and life factors contributing to active longevity.